Edukasi dan Pencegahan Pergaulan Bebas bagi Remaja Desa melalui Program LANCER sebagai Sarana Penguatan Nilai Sosial Positif di Desa Kedak - Yulaikha, Aida Ayu; Alfiyah, Putri Fakhidatul; Setiawan, Muhamad Wahyuli; Alfuadi, Achmad Fatoni; Nashrullah, Ahmad; Prameswari, Amanda Dwi; Tutuko, Andiny Septi Nurqoyyuum; Saimon, Aqsha Bin; Putri, Ayu Septiana; Choirunnisa, Ayuna; Anggraini, Denada Catur Puri; Egistika, Dewi Chofshoh; Handoko, Fahrizal Surya; Nisa, Khoirun; Alawiyah, Qothrunnada Lu'luatul; Wati, Susi Rahma; Asfia, Uyunu Zam-Zami; Fikriyah, Vanida (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The program implemented in Kedak Village aims to increase adolescent awareness of the importance of building healthy social relationships and preventing promiscuity. This program aims to strengthen positive social values through collaboration with the Youth Posyandu. The methods used include a community-based approach, educational activities, group discussions, and direct socialization. The program involves adolescents, the local community, and support from educational institutions and the village government. The results of the program show active participation of adolescents and positive acceptance from the community. However, the significant impact on changes in social behavior has not been fully measured. The conclusion of this program emphasizes the importance of synergy between various parties to create an environment that supports adolescent development. Future recommendations are to improve monitoring, evaluation, and development of follow-up programs to maintain the sustainability and effectiveness of this community service.